A Golden Rule for Social Investments: How to Do It - Cinzia Alcidi; Francesco Corti; Daniel Gros (Intereconomics, 2022)
The idea of a golden rule has recently been relaunched in the framework of the debate on the European Green Deal.
Keywords: H5; 330